P506 The Impact of Anxiety in Patients With Inflammatory Bowel Diseases Treated With Biologics during COVID Lockdown. A Comparative Study between Hospitalized and non-hospitalized patients. (27th May 2021) - Bertani, L; Barberio, B; Zanzi, F; Maniero, D; Ceccarelli, L; Marsilio, I; Minciotti, M; Coppini, F; Lorenzon, G; Mumolo, M G; Zingone, F; Costa, F; et al.
Abstract: Background: The first wave of COVID-19 pandemic management implied to remain at home in order to reduce the spread of the infection. Several patients with inflammatory bowel diseases (IBD) treated with biologics had to go to the hospital to perform intravenous (i.v.) therapies, whereas patients treated with subcutaneous (s.c.) ones could remain at home. Since immumodulatory therapies as well as the access to high-risk places like hopitals have been associated to an increased risk of infections, we have investigated whether patients hospitalized or treated at home showed similar levels of anxiety related to the pandemic situation. Methods: We conducted a survey including consecutive IBD patients treated with biologics at three Italian referral centers referring to the first lockdown period. We included consecutive adult patients in clinical and biochemical remission treated with biologics, administered i.v. or s.c. Patients experiencing a disease flare during these months were excluded from the study, in order to avoid potential biases related to disease activity. Patients underwent the normally scheduled clinical visits, performed at home by using phone or video calls for patients treated with s.c. drugs and only in specific cases (i.e. suspected COVID symptoms) for patients treated with i.v. ones. We administered to all patients the Hospital Anxiety and Depression Scale (HADS) questionnaire and other 11 questions, specifically related to COVID and its implications. Group differences in continuous and nominal variables were tested by Kruskal–Wallis test and Fisher exact test, respectively. Results: A total of 189 IBD patients were recruited, 112 (59.3%) treated with i.v. drugs and 77 (40.7%) with s.c. ones. The two groups of patients had similar scores in the 14 single items of the HADS questionnaire (p>0.10 for all). The total HADS score obtained by the sum of all items was also almost identical between groups (37.1 ± 2.8 vs 37.2 ± 2.8; p=0.98). In patients treated with i.v. drugs receiving a televisit (n=17), the rates of satisfaction about telemedicine (58.8%) and the lack of in-person care (33.3%) were significantly lower compared with those treated with s.c. drugs (94.8% and 92.2%, respectively; both p<0.0005). Conclusion: Our results suggest that there is no need to convert patients from i.v. to s.c. therapy, since the risk of infection as well as of disease relapse due to stressful events are similar in both groups. Moreover, the hospitalization for drug administration does not affect the the psychological status of the patients. Interestingly, patients used to coming to the hospital have more need for in-person contact than patients used to be treated at home, suggesting that the choice of telemedicine should be personalized.